1999
DOI: 10.1523/jneurosci.19-08-03238.1999
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms for Age-Related Changes of Fingertip Forces during Precision Gripping and Lifting in Adults

Abstract: We investigated changes across the adult life span of the fingertip forces used to grip and lift objects and their possible causes. Grip force, relative safety margin (grip force exceeding the minimum to avoid slip, as a fraction of slip force), and skin slipperiness increased beginning at age 50 years. Skin slipperiness explained relative safety margin increases until age 60 years. Hence, after age 60 years, additional factors must elevate grip force. We argue that one factor is impaired cutaneous afferent en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
168
2
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 172 publications
(189 citation statements)
references
References 47 publications
18
168
2
1
Order By: Relevance
“…Therefore, despite maintaining the ability to reduce post-synaptic GABAA-mediated inhibition within motor cortex during tonic muscle activation, old adults demonstrate a reduced modulation of inhibitory tone for tasks requiring more complex activation of primary motor cortex. This may contribute to age-related impairments in motor performance during this task, as has been shown previously [43,44]. Alternatively, a recent study by Fujiyama and colleagues [21] showed that greater SICI during the foreperiod of a warned reaction task was associated with faster reaction times in old but not young subjects.…”
Section: Effects Of Age On Short-interval Intracortical Inhibitionmentioning
confidence: 70%
“…Therefore, despite maintaining the ability to reduce post-synaptic GABAA-mediated inhibition within motor cortex during tonic muscle activation, old adults demonstrate a reduced modulation of inhibitory tone for tasks requiring more complex activation of primary motor cortex. This may contribute to age-related impairments in motor performance during this task, as has been shown previously [43,44]. Alternatively, a recent study by Fujiyama and colleagues [21] showed that greater SICI during the foreperiod of a warned reaction task was associated with faster reaction times in old but not young subjects.…”
Section: Effects Of Age On Short-interval Intracortical Inhibitionmentioning
confidence: 70%
“…The higher SM in the current study might be explained by the nature of the handle used in the present study; it was heavy with expensive force transducers attached but was freely held in space with no safety catch in the event of dropping. This is reminiscent of the "better safe than sorry" strategy documented for special populations (e.g., in elderly: Cole et al 1999;Shim et al 2004, andin cerebellar patients: Babin et al 1999;Fellows et al 2001). …”
Section: Task-specific Variations In the Safety Marginmentioning
confidence: 97%
“…The prehension literature details many task-dependent instances of mechanically unnecessary force production (e.g., Latash et al 1998a,b;Cole et al 1999;Zatsiorsky et al 2000). Some of these effects were described as "enslaving" (Kilbreath and Gandieva 1994;Zatsiorsky et al 2000;Schieber 2001) and were attributed to a feed-forward controller to physiologically connected effectors (Latash et al 1998a,b).…”
Section: Mechanically Unnecessary Forcesmentioning
confidence: 99%
“…Proprioception also decreases with age and is closely related to loss of muscle and joint strength. Muscle strength has been found to remain stable until the fifth or sixth decade, but shows a 50 % decrease by age 80 (Cole et al 1999;Sturnieksa et al 2008). The winning performance of Senior Olympians ([50 years) declines approximately 3.4 % per year over 35 years of competition: slowly from age 50 to 75 years and then dramatically after age 75 years (Wright and Perricelli 2008).…”
Section: Introductionmentioning
confidence: 99%